COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN ISLAMIC COMMERCIAL BANKS AND CONVENTIONAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2017-2021 - Nurjannah; Abdul Wahid Mongkito; Putri Wulansari; Muljibir Rahman (Academic Bright Collaboration, 2025)
This study aims to analyze the differences and compare the average financial performance between Islamic Commercial Banks and Conventional Banks using six financial ratios: Capital Adequacy Ratio (CAR) as a proxy for capital, Non-Performing Loan (NPL) for asset quality, Return on Assets (ROA) for profitability, Return on Equity (ROE) for profitability from equity, Operational Efficiency Ratio (BOPO), and Loan to Deposit Ratio (LDR) for liquidity. This research employs a quantitative descriptive approach using secondary data derived from financial statements of banks listed on the Indonesia Stock Exchange. The analysis technique applied is the Independent Sample T-test to examine the differences in the average financial performance between Islamic and conventional banks. The results indicate that there are significant differences in the average financial performance between Islamic and conventional banks in terms of CAR, NPL, and BOPO. However, no significant differences are found in ROA, ROE, and LDR. Based on mean values, Islamic banks demonstrate better performance in CAR and ROA, while conventional banks outperform in NPL, ROE, BOPO, and LDR. Overall, conventional banks show superior financial performance compared to Islamic banks, which is attributed to their longer operational experience and more established market presence. This study contributes to the comparative financial performance literature by providing empirical evidence on the relative strengths and weaknesses of Islamic and conventional banking systems in Indonesia using multiple financial indicators. It offers valuable insights for policymakers, practitioners, and academics in evaluating the competitiveness and development of the Islamic banking sector.